Does women's status matter for food security? Evidence from Bangladesh - Mohammad A. Razzaque; Mohammad Mokammel Karim Toufique (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
Using data from a survey of Bangladeshi households, this paper investigates the link between female status and food security. Employing three different indicators of female status – husband's and wife's assets brought at marriage, female share of household income and a composite index of women empowerment, the paper finds evidence of women's status influencing food security. By raising the level of food security for some disadvantaged women's groups female status is also found to be instrumental in mitigating the extent of gender-based within-household discrimination. The findings reveal that inferences drawn about food security by observing the changes in various non-food budget shares could be misleading or overemphasized.
Keywords: D13; D63; I0; O53; 330; food security; women's status; intra-household distribution; gender discrimination; Bangladesh; Frauen; Geschlechterdiskriminierung; Nahrungsmittelversorgung; Privater Haushalt; Bangladesch